Single particle fluorescence imaging of perovskite nanocrystal crystallization for illustrating coupled nucleation-and-growth - Lige Liu; Dashan Dong; Zhiwei Long; Wanxue Wei; Chang Sun; Wei Liu; Xiaoshuai Huang; Liangyi Chen; Haizheng Zhong; Kebin Shi (Nature Communications)
Abstract Because of the lack of spatiotemporal characterization techniques, it has been of great challenge to investigate the crystallization of nanocrystals. With a high-speed structured illumination super-resolution fluorescence microscopy (SIM), we hereby report an in situ fluorescence imaging technique to monitor the crystallization of perovskite nanocrystals at single-particle level. By correlating the fluorescence intensity with particle size, we illustrate the coupled nucleation-and-growth of perovskite nanocrystals in polymer matrix. The temporal fluorescence intensity analysis of individual nanocrystals reveals the diffusion-controlled growth process with a fast growth at the beginning followed by a slow growth. The analysis of ensemble nanocrystals illustrates the evolution of nucleation rate with the change of precursor concentrations. We further analyze the Gibbs free energy fluctuation of couple nucleation-and-growth. The growth free energy dominates in the continuous nucleation of perovskite nanocrystals, which accounts for the narrow size distribution. In comparison with LaMer model, the coupled nucleation-and-growth provides an alternative model to fabricate narrow sized nanocrystals.